How Chinese Design Standards Contribute to Low Value Add and Poor Product Quality - Seidelson, Craig (Journal of Strategic Innovation and Sustainability, 2020)
China is home to approximately 36,000 foreign invested enterprises (Zimmerman, 2012). A perception these companies are keenly interested in perpetuating is that products made in China from imported designs are of superior quality. Apple Inc. is at the forefront of this approach labeling each of its 34.6 million iPhones “Designed by Apple in California. Made in China.” (Clover, 2019). In actuality, once foreign designs are in China many are changed to be in compliance with national, provincial and professional standards. This paper shows how adherence to Chinese design standards can negatively impact value added manufacturing and product quality.